STUDY ON THE FRUIT MORPHOLOGY OF MAPANIA SPECIES (CYPERACEAE) EASTERN NORTH OF SARAWAK - Miraadila, M.I.; Meekiong, Kalu; Shabdin, Z.; Ivy Geradlyn, N.; Aimi Syazana, Sedek; Syauqina, M.Y. (2019)
The study of fruit morphology of Mapania species from Eastern North of Sarawak is presented in this paper. The samples were collected from various localities in the Eastern North of Sarawak, includes Lambir Hills National Park (LHNP), Bukit Sembiling Nature Reserve (BSNR), Ulu Mentawai, Mulu National Park (UMMNP), Long Banga (LB) and Tama Abu Production Forest (TAPF). Matured fruits were obtained by dissecting the spike. Morphological characteristics were observed use USB Portable Microscopes (500x) and parameters were measured use digital caliper. The morphological characteristics were compared and analyzed. Fruits of M. meditensis were the biggest (9 mm long, 4.25 mm diam.) and the smallest fruit was M. debilis (2.45 mm long, 1.5 mm diam.). Overall the fruit morphological was very useful to differentiate the species level particularly the sizes, exocarp appearance and the present of costae.